KONTRIBUSI EFEKTIVITAS MANAJEMEN EKSTRAKURIKULER TERHADAP PRESTASI SEKOLAH NON AKADEMIK - Astafiyah Astafiyah (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2018)
The objectives of this study are (1) to describe the level of extractive management effectiveness in Serang Junior High School 18; (2) to describe how much non-academic school achievement; (3) describes how much extracurricular non-academic school achievements. The research method used in this study is a quantitative method, with a correlational approach. The population in this study were students who took extracurricular activities as many as 120 students, thus the study sample was 30 respondents. The data collection techniques used a questionnaire. The conclutions of the research results are (1) the level of extracurricular management effectiveness at Serang Junior High School 18 is classified as good with 59.19%; (2) the level achievement of non-academic schools in Serang Junior High School is classified as good with 63.41%; and (3) the contributions of the effectiveness of extracurricular management variables on the achievement of non-academic school at 38.44%. Keywords. Effectiveness, extracurricular management, non-academic achievements.